Effect of Coastal Social Environment on the Character of Early Childhood in PAUD Amal Saleh Foundation - Rismawati Rismawati; Ummul Khair Rahmah; Dela Febrian; Arindha Sukma; Syuraini Syuraini (Universitas Negeri Padang, 2020)
This study aims to look at the effect of the coastal environment on the character of early childhood in the PAUD Amal Saleh Foundation. The study uses descriptive survey research that is explanatory research. Data obtained from this research will be processed through descriptive statistics, then confirmed again in the field through in-depth interviews, observations, and documentation studies in order to obtain comprehensive research answers. The sample taken here is an early childhood from the coast which has a bad character, which is as many as 7 people. The instrument used in the form of a questionnaire will be asked to the PAUD educator about the characteristics of early childhood. The questionnaire was arranged as an interview guide. The questionnaire was intended for all three children who had problems with their bacteria. The results of this study indicate that the environment has a significant influence on the character of early childhood. Early childhood who live on the coast will have a different character from early childhood who live at home. The results showed significant results. The character is influenced by one's living environment. If the environment is good, then it can be ensured that the person's character will also be good.Keywords: Environmental Influence, Early Childhood, Character